Sustained STING-IRF7 signaling aggravates LPS-induced endometrial inflammation via excessive neutrophil extracellular traps generation - Chu, Min; Ma, Ding; Song, Zhan; Liang, Li; Xing, Fengjuan; Bao, Hongchu (Frontiers in Immunology, 2026)
IntroductionThe stimulator of interferon genes (STING) is a central mediator of innate immune sensing and represents a critical regulator of chronic inflammation. Upon persistent infection, excessive neutrophil activation leads to the formation of neutrophil extracellular traps (NETs) that damage the tissues. However, the mechanism by which STING signaling regulates NETs formation under chronic inflammatory conditions remains poorly understood.MethodsIn this study, using LPS-induced murine endometritis models in wild-type and STING-deficient mice, we demonstrated that STING deficiency significantly suppressed myeloperoxidase activity, and diminished NETs formation.ResultsWe identified neutrophil surface molecular CD11b as a key downstream target of STING, whose expression was transcriptionally regulated via IRF7. Furthermore, the STING-IRF7 axis was found to drive lipocalin-2 (LCN2) expression, which acted through its receptor MC4R to upregulate intracellular adhesion molecule-1 (ICAM-1), thereby facilitating neutrophil recruitment and NETosis during LPS stimulation. The role of this pathway was validated both in vitro using isolated neutrophils and in vivo using Lcn2-/- mice. Moreover, STING deficiency reprogramed the endometrial immune microenvironment by reducing inflammatory infiltration and restoring receptivity transcription factor homeobox A10 (HOXA10).DiscussionOur findings revealed a novel mechanism in which the STING-IRF7 pathway exacerbated endometrial inflammation and tissue damage by coordinately upregulating CD11b and activating the LCN2-ICAM-1 axis. Consequently, targeting the STING signaling pathway may offer a promising therapeutic strategy for chronic endometritis.